2022
DOI: 10.1101/2022.07.07.499200
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CBP60-DB: An AlphaFold-predicted plant kingdom-wide database of the CALMODULIN-BINDING PROTEIN 60 (CBP60) protein family with a novel structural clustering algorithm

Abstract: Molecular genetic analyses in the model species Arabidopsis thaliana have demonstrated the major roles of different CAM-BINDING PROTEIN 60 (CBP60) proteins in growth, stress signaling, and immune responses. Prominently, CBP60g and SARD1 are paralogous CBP60 transcription factors that regulate numerous components of the immune system, such as cell surface and intracellular immune receptors, MAP kinases, WRKY transcription factors, and biosynthetic enzymes for immunity-activating metabolites salicylic acid (SA) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In this paper, we have successfully identified and characterized 11 CBP60 family members in tomato plants. Unlike CBP60 proteins in the model species Arabidopsis thaliana (Reddy et al, 2002;Wang et al, 2009;Truman et al, 2013;Amani et al, 2022;Zheng et al, 2022), CBP60 proteins in tomato and other species have remained unexplored. First, phylogenetic and structural analyses were conducted for the 11 SlCBP60 proteins (Figures 1-2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we have successfully identified and characterized 11 CBP60 family members in tomato plants. Unlike CBP60 proteins in the model species Arabidopsis thaliana (Reddy et al, 2002;Wang et al, 2009;Truman et al, 2013;Amani et al, 2022;Zheng et al, 2022), CBP60 proteins in tomato and other species have remained unexplored. First, phylogenetic and structural analyses were conducted for the 11 SlCBP60 proteins (Figures 1-2).…”
Section: Discussionmentioning
confidence: 99%
“…CBP60g is a member of the CBP60 protein family (Reddy et al, 2002; Wang et al, 2009; Truman et al, 2013; Amani et al, 2022; Zheng et al, 2022) and serves as a key transcriptional regulator for SA biosynthetic genes ISOCHORISMATE SYNTHASE 1 ( ICS1 ) and AVRPPHB SUSCEPTIBLE 3 ( PBS3 ; Zhang et al, 2010; Wang et al, 2009; Sun et al, 2015; Kim et al, 2022). Like CBP60g, another CBP60 protein family member SYSTEMIC ACQUIRED RESISTANCE 1 (SARD1) plays a partially redundant role in SA biosynthesis (Zhang et al, 2010; Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a recent study reported orthologs of CBP60g and SARD1 in tobacco plants (Takagi et al, 2022), the function and regulation of CBP60 proteins in other plant species have yet to be investigated. We recently identified CBP60 homologs across various representative taxa in the plant kingdom (Amani et al, 2022); however, whether gene expression trends observed in Arabidopsis are conserved in other plants remain unclear. In this study, we report the identification of 11 homologous CBP60 (SlCBP60) genes in tomato plants (Solanum lycopersicum).…”
Section: Introductionmentioning
confidence: 99%